Linking national innovation systems and innovation capacity - Metaiche, Mohammed El Amine (Management and Entrepreneurship: Trends of Development, 2024)
National Innovation Systems (NIS) are fundamental in shaping a country’s innovation capacity, influencing economic diversification and sustainable growth. The purpose of this study is to examine the role of well-structured and functional NIS in fostering innovation capacity across diverse contexts, including resource-rich countries, leading innovative nations, and developing regions. This research employs a comparative analysis methodology, drawing on data from global innovation indices, case studies, and academic literature to evaluate key metrics such as R&D investment, patent activity, university-industry collaboration, and public-private partnerships. The findings reveal significant disparities in innovation performance, with resource-rich countries often constrained by systemic challenges like the "resource curse," while nations such as Norway and Canada illustrate how strategic management of natural wealth drives sustainable innovation. Similarly, developing regions face barriers including weak institutional frameworks and limited funding, yet exhibit potential for progress through targeted reforms. The findings underline the importance of robust NIS structures, emphasizing the need for greater investment in R&D, stronger university-industry collaboration, and enhanced public-private partnerships as crucial enablers of innovation capacity. Practical and policy implications are needed in offering actionable strategies for overcoming systemic challenges, improving innovation ecosystems, and achieving economic resilience. Jel Classification: O31, O32, R11, O57